Simulated Weightlessness Perturbs the Intestinal Metabolomic Profile of Rats - Jin, Mingliang; Wang, Jiaojiao; Zhang, Hao; Zhou, Hongbin; Zhao, Ke (Frontiers in Physiology, 2019)
Recently, disorders of intestinal homeostasis in the space environment have been extensively demonstrated. Accumulating evidence have suggested microgravity and simulated weightlessness could induce dysbiosis of intestinal microbiota, which may contribute to the bowel symptoms during spaceflight. However, the specific responses of intestinal metabolome under simulated weightlessness and its relationship with the intestinal microbiome and immune characteristics remain largely unknown. In the current study, 20 adult Sprague-Dawley (SD) rats were randomly divided into the control group and the simulated weightlessness group using a hindlimb unloading model. The metabolomic profiling of cecal contents from 8 rats of each group was investigated by gas chromatography-time of flight/mass spectrometry. The significantly different metabolites, biomarkers, and related pathways were identified. Multivariate analysis, such as principal component analysis and orthogonal projections to latent structures-discriminant analysis, demonstrated an obvious separation between the control group and the simulated weightlessness group. Significantly different metabolites, such as xylose, sinapinic acid, indolelactate and digalacturonic acid, were identified, which participate in mainly pyrimidine metabolism, pentose and glucuronate interconversions, and valine, leucine and isoleucine metabolism. Cytidine-5'-monophosphate, 4-hydroxypyridine and phloretic acid were determined as pivotal biomarkers under simulated weightlessness. Moreover, the significantly different metabolites were remarkably correlated with dysbiosis of the intestinal microbiota and disturbance of immunological characteristics induced by simulated weightlessness. These metabolic features provide crucial candidates for therapeutic targets for metabolic disorders under weightlessness.